A poesia mística de São João da Cruz em perspectiva dialógica - Lima, Marcelo Tomaz de (2019)
Since former times, mystical poetry describes, in poem verses, the itinerary that leads the soul to its union with God. So we start from texts that (re) reveal mystical experiences (the mystery of the mystic's encounter with God or, with the Other Absolute, before which the experience of the Sacred breaks out) to delimit our corpus. The objective of this research is to analyze the dialogical relations between the poems of St. John of the Cross and the religious discourse of Song of Songs, seeking to ascertain what valuations are produced by the poet when resuming this biblical literature, observing the axiological positioning of this subject “poetic speaker". The theoretical underpinning of this research lies in Bakhtin's philosophical-literary writings and the Circle, which constitute the Dialogical Theory of Language. The question that will permeate the analysis of poems will be: How do the mystic's meanings occur in the poems, based on the dialogic relations he establishes with other utterances? This research intends to analyze the statements of the poems Dark Night and Flame of Love, written by Saint John of the Cross, taking into consideration the environment and the social horizon in which these poems could materialize. This is a bibliographical, documentary, descriptive and qualitative research, in which we intend to interpret data collected in the poems, and this interpretation results from the dialogical relations between the above poems. The theoretical, methodological and analytical constructions presented here contributed to our defense that the senses of the mystic manifest themselves in the poetry of St. John of the Cross, through the style and expressiveness of various statements, revealing the loving relationship between Beloved and Beloved, between God and St. John of the Cross, between God and the church. We conclude, therefore, from the theoretical and analytical paths presented here, about the notion of discourse in poetry, that although prose was the great theme of Bakhtin's work, an overview of the whole Bakhtinian work reveals the impossibility of closing it in the concept of prose, in the genre prose. Prose and poetry are, at bottom, two distinct moments of apprehension of the language of others.